A Consensus Molecular Classification of Muscle-invasive Bladder Cancer - Kamoun, Aurélie; de Reyniès, Aurélien; Allory, Yves; Sjödahl, Gottfrid; Robertson, A. Gordon; Seiler, Roland; Hoadley, Katherine A.; Groeneveld, Clarice S.; Al-Ahmadie, Hikmat; Choi, Woonyoung; Castro, Mauro A.A.; Fontugne, Jacqueline; et al. (European urology, 2020)
Muscle-invasive bladder cancer (MIBC) is a molecularly diverse disease with heterogeneous clinical outcomes. Several molecular classifications have been proposed, but the diversity of their subtype sets impedes their clinical application. To achieve an international consensus on MIBC molecular subtypes that reconciles the published classification schemes. We used 1750 MIBC transcriptomic profiles from 16 published datasets and two additional cohorts. We performed a network-based analysis of six independent MIBC classification systems to identify a consensus set of molecular classes. Association with survival was assessed using multivariable Cox models. We report the results of an international effort to reach a consensus on MIBC molecular subtypes. We identified a consensus set of six molecular classes: luminal papillary (24%), luminal nonspecified (8%), luminal unstable (15%), stroma-rich (15%), basal/squamous (35%), and neuroendocrine-like (3%). These consensus classes differ regarding underlying oncogenic mechanisms, infiltration by immune and stromal cells, and histological and clinical characteristics, including outcomes. We provide a single-sample classifier that assigns a consensus class label to a tumor sample’s transcriptome. Limitations of the work are retrospective clinical data collection and a lack of complete information regarding patient treatment. This consensus system offers a robust framework that will enable testing and validation of predictive biomarkers in future prospective clinical trials. Bladder cancers are heterogeneous at the molecular level, and scientists have proposed several classifications into sets of molecular classes. While these classifications may be useful to stratify patients for prognosis or response to treatment, a consensus classification would facilitate the clinical use of molecular classes. Conducted by multidisciplinary expert teams in the field, this study proposes such a consensus and provides a tool for applying the consensus classification in the clinical setting. An international consortium of bladder cancer expert teams establishes a consensus reconciling the diverse molecular classifications of muscle-invasive bladder cancer. This work offers a robust framework that will enable testing and validating predictive biomarkers in future prospective clinical trials.